Contrasting definitions and incidence of healthcare-associated respiratory viral infections in a pediatric hospital. (23rd March 2022) - Most, Zachary M.; Jackson, Patricia; Sebert, Michael; Perl, Trish M.
Abstract: Objective: To determine the difference in the incidence of healthcare-associated respiratory viral infection (HARVI) in a pediatric hospital depending on the definition used. Design: Descriptive historical cohort study. Setting and participants: Patients aged 0–21 years old who were admitted between July 2013 and June 2018 to a 490-bed primary to quaternary-care pediatric hospital serving northern Texas. Methods: HARVI was defined using microbiologic confirmation, development of new symptoms while hospitalized, and exposure time greater than the minimum incubation period for each specific virus. Events that occurred following the maximum incubation period for that virus were classified as definite, otherwise they were classified as possible. This definition was compared to definitions using alternate timing of onset and symptomatology requirements. Data pertaining to demographics, diagnoses, and illness severity were collected. Results: In total, 498 HARVIs (320 definite and 178 possible) were identified, with an incidence rate of 0.98 per 1, 000 patient days (0.63 and 0.35, respectively). Rhinovirus or enterovirus and respiratory syncytial virus were the most identified viruses (58% and 10%, respectively). The median time from admission until HARVI was 10.5 days (interquartile range [IQR], 5–30 days). When alternate definitions were employed, the incidence of HARVI ranged from 0.96 to 2.00 per 1, 000 admitted patient days. Conclusions: HARVI remain a common nosocomial infection in pediatric hospitals and the measured incidence is dependent on the definition used. Because of the endemic and pandemic potential of respiratory viruses, standardized definitions are needed to facilitate intra- and interhospital comparisons.